PENGARUH DANA BAGI HASIL TERHADAP BELANJA DAERAH DI KABUPATEN GORONTALO UTARA - Aliu, Siskawati D.; Makur, Dharmawaty S.; Yusuf, Fitria Melynsyah (Program Studi Akuntansi, 2021)
This research was conducted at the Regional Financial and Asset Agency of Gorontalo Utara Regency. The objective was to see the effect of the independent variable, namely profit sharing, on the dependent variable, namely regional expenditure. This research uses a simple linear regression method. The results indicated that profit-sharing has a positive and significant effect on regional spending. If the profit-sharing funds are greater or have increased, regional spending will increase by 0.749, seen from the results of the regression coefficient. If the profit-sharing funds have increased by 1%, then regional spending will increase by 0.749.